Antimicrobial Susceptibility Pattern of Bacteria Isolated from Blood Urine and Wound Swab in Febrile Neutropenic Children in a Tertiary Level Hospital, Bangladesh. - Ahamed, Farook; Shahid, Sazzad Bin; Begum, Shahin Ara; Mohammad Jobayer, -; Rahman, Mizanur; Nahar, Sultana Shazeda; Islam, Afiqul (Bangladesh Journal of Medical Microbiology, 2017)
Fever is the commonest symptom of infection in neutropenic children with malignancy, under chemotherapy. To avoid bacterial complications, it is necessary to diagnose infection early and to administer empirical antibiotic. The aim of this study was to find out the causative bacteria and their antimicrobial susceptibility pattern in febrile neutropenic children who were under chemotherapy. The study was conductedin a tertiarylevel hospital,Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Blood, urine and wound swab were collected for culture from 30 febrile neutropenic children, age 1-15 years. Out of 70 samples total 26(37.14%)yielded growth of bacteria among which 6(20%), 12(40%), and 8 (80%) were isolated from blood, urine and wound swab respectively. Among thebacteria Pseudomonas spp, Esche coli and Staph aureus weremost frequently isolated. Meropenem, imipenem and netilmicin were the most sensitive against gram negative bacteria and the entire isolated gram positive bacteria were 100% sensitive to vancomycin and linezolid. Bangladesh J Med Microbiol 2017; 11 (2): 5-8